Neuroimaging chronic pain: what have we learned and where are we going?. (October 2014) - Martucci, Katherine T; Ng, Pamela; Mackey, Sean
ABSTRACT : Advances in neuroimaging have helped illuminate our understanding of how the brain works in the presence of chronic pain, which often persists with unknown etiology or after the painful stimulus has been removed and any wounds have healed. Neuroimaging has enabled us to make great progress in identifying many of the neural mechanisms that contribute to chronic pain, and to pinpoint the specific regions of the brain that are activated in the presence of chronic pain. It has provided us with a new perception of the nature of chronic pain in general, leading researchers to move toward a whole-brain approach to the study and treatment of chronic pain, and to develop novel technologies and analysis techniques, with real potential for developing new diagnostics and more effective therapies. We review the use of neuroimaging in the study of chronic pain, with particular emphasis on magnetic resonance imaging.